2016
DOI: 10.1089/mdr.2015.0194
|View full text |Cite
|
Sign up to set email alerts
|

Holarrhena antidysenterica Extract and Its Steroidal Alkaloid, Conessine, as Resistance-Modifying Agents Against Extensively Drug-Resistant Acinetobacter baumannii

Abstract: Emergence and spread of antibiotic-resistant Acinetobacter baumannii have become a major public health concern. This study was designed to investigate the efficacy of Holarrhena antidysenterica extract and its major steroidal alkaloid conessine as resistance-modifying agents (RMAs) on the susceptibility of A. baumannii to novobiocin and rifampicin. A significant synergistic activity of both the extract and conessine in combination with either novobiocin or rifampicin with fractional inhibitory concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…The susceptibility of the P. aeruginosa strains to a group of anti-pseudomonal antibiotics alone or in the presence of steroidal alkaloids (128 or 1024 mg/L) or conessine (32 mg/L) is shown in Table 1 . In this study, steroidal alkaloids extract at 1024 mg/L contained approximately 37 mg/L conessine content [ 19 ]. The strain overexpressing the MexAB-OprM efflux pump (PAM1032) was more resistant to ceftazidime, piperacillin, meropenem and levofloxacin in comparison to the parent strain (PAM1020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The susceptibility of the P. aeruginosa strains to a group of anti-pseudomonal antibiotics alone or in the presence of steroidal alkaloids (128 or 1024 mg/L) or conessine (32 mg/L) is shown in Table 1 . In this study, steroidal alkaloids extract at 1024 mg/L contained approximately 37 mg/L conessine content [ 19 ]. The strain overexpressing the MexAB-OprM efflux pump (PAM1032) was more resistant to ceftazidime, piperacillin, meropenem and levofloxacin in comparison to the parent strain (PAM1020).…”
Section: Resultsmentioning
confidence: 99%
“…Steroidal alkaloids present within the extracts possess antibacterial, anti-diarrhoeal and astringent properties [ 15 , 16 ]. Previous studies indicated that H. antidysenterica extract, and the principal active ingredient alone (the steroidal alkaloid conessine [ 16 ]), were able to restore the inhibitory activity of novobiocin and rifampicin against extensively drug-resistant Acinetobacter baumannii in vitro [ 17 19 ]. Exposure to either H. antidysenterica extract, or conessine alone, at concentrations that did not result in increased membrane disruption, resulted in accumulation of the fluorescent dye Pyronin Y suggesting that both treatments may have EPI-like properties [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, PAβN at 10 μg/ml decreased predominantly MIC concentrations of trimethoprim, clindamycin and chloramphenicol [97] [102]. Twice a time on clinical isolates, whereas PAβN at 20 μg/ml reduced nicidixic acid MIC to 16-fold but showed little effect on sensitiveness to ciprofloxacin [106]. At 100 μg/ml PAβN are also sensible minocycline activity by decreasing ≥ 04-fold MIC values [107].…”
Section: Mechanisms Of Efflux Pumps Inhibitors (Epi)mentioning
confidence: 86%
“…It has been demonstrated that the extract potentiated the effect of antibiotics by acting as a permeabilizer [ 13 ]. Moreover, a recent study indicated that both Holarrhena antidysenterica extract and conessine, a steroidal alkaloid compound, could restore antibiotic activity due to interference with AdeIJK pump in A. baumannii [ 14 ]. Previous study documented that AdeIJK pump and MexAB-OprM pump are functionally equivalent pumps in both organisms [ 15 ].…”
Section: Introductionmentioning
confidence: 99%